Tecnologias educacionais como recurso pedagógico em tempos de covid-19 - LIMA, Rosana do Socorro Campos (Instituto Federal do Amapá, 2021)
At the beginning of the 21st century, humanity was surprised by the pandemic unleashed by Covid-19 and it was necessary to change behavior in all segments, including education. Educators were required to have skills with Digital Information and Communication Technologies (TDIC), which started to be used daily in the reality in which the pandemic is facing. This article analyzes the process of mediation of teaching and remote learning through educational technologies. Therefore, Moran (2018), Cordeiro (2020) and Matias et al (2020) are taken as the main theoretical framework. This work has a qualitative and quantitative approach, and is defined as applied exploratory research which highlights the possibilities of learning strategies through digital technologies. Research subjects are professors and students from a state university in Amapá of a specific course who answered a questionnaire with open and closed questions. It appears that the lack of infrastructure to carry out the activities are the elements identified as major obstacles in the success of remote classes, however, the digital medium, offers numerous effective remote mediation resources for educational use, knowing how to use and handle becomes indispensable factor in the present times.